Characteristics of plasma electrolytic oxidation coatings on 6061 al alloy prepared at different current densities - Tran, Quang-Phu; Dao, Van-Da; Pham, Van-Hoi (Vietnam Journal of Science and Technology, 2020)
Plasma electrolytic oxidation (PEO) has earned much attention due to its powerful and easy formation of hard and corrosion-resistant oxide layers on valve metals, such as Al alloys. Here we report the effects of current density (CD) on microstructure and properties of coatings on 6061 Al alloy by PEO using direct current mode. The electrolyte contains the chemicals of Na2SiO3, Na2WO4´2H2O, and NaH2PO2´H2O. The CDs adopted 5.0, 7.5, 10.0, and 12.5 A/dm2, respectively, for a fixed PEO time of 30 min. The thickness, surface morphology, phase composition, hardness, and corrosion resistance of PEO coatings as the function of the applied CD have been studied and discussed. Studied results show the coating thickness is proportional to the applied CD. When the applied CD increases 2.5 times from 5.0 to 12.5 A/dm2, the growth rate of oxide layers increased by more than 3.5 times, from 0.423 to 1.493 μm/min, respectively. SEM images are characterized by a reduction in the ratio of agglomerate-bumps-region/flatten-region as applied CD increases. However, cracks and larger pores appear when the applied CD is higher than 10.0 A/dm2. X-ray diffraction pattern shows that the main phases of Al, g-Al2O3, α-Al2O3, and W are contained in all coatings. PEO coated sample has the highest hardness of 1290 HV and highest polarization resistance of 8.80 ´ 106 Wcm2 obtained at applied CD 10 A/dm2 which shows the best performance of the coating. The variation in coating performance is explained by microstructure details, specifically phases, compositions of oxide-layers, and micro-pores and cracks.